Role of chemical exposure in the incidence of vitiligo: a case–control study in Tunisia. Issue 1 (31st December 2023) - Rmadi, Nehla; Kotti, Nada; Bahloul, Emna; Dhouib, Feriel; Sellami, Imen; Sellami, Khadija; Jmal Hammami, Kaouthar; Masmoudi, Mohamed Larbi; Turki, Hamida; Hajjaji, Mounira
ABSTRACT: Vitiligo is a multifactorial dermatosis with many etiological hypotheses that have been suggested for its occurrence. To our knowledge, few epidemiological studies are available on vitiligo induction factors and particularly on the role of exposure to chemicals in the onset of the disease has been found. Therefore, there is need to investigate the relationship between vitiligo and chemical exposures in order to understand this mysterious disease. We conducted a case–control study of patients with vitiligo whose diagnosis was made by a specialist in dermatology. The total study period was of 6 months extending from 1 July to 31 December 2019. The minimum sample size was determined as 46 cases and 92 controls. The control group was gender, age, and professional status matched to the vitiligo group. In the binary logistic regression model, household chemicals/colored toothpaste use, a history of a repeated antibiotic use, and an occupational exposure to phenol/catechol derivatives were significantly associated with vitiligo (three to fourfold increase). Our results suggest that chemical factors play a key role in the occurrence of vitiligo. Therefore, prevention of this dermatosis requires the identification of exposure to the incriminated chemicals in any patient followed for vitiligo. The earlier the diagnosis of 'chemical' or chemically aggravated vitiligo, the better the prognosis for this disease.